Análisis bromatológico de leche fresca procedente de los clubes de madres del programa social del vaso de leche de la municipalidad provincial de trujillo en los meses de mayo – junio del 2010 - Lecca Luján, Nélida Pelly (2010)
This research aims at realizing the "Chemical composition analysis of fresh milk coming from mothers clubs social program of Vaso de Leche of the Provincial Municipality of Trujillo from of May to June 2010" and to verify if it complies with the quality standards parameters established in the Peruvian Technical Standard PTS 202.001:2010, which was used for 840 samples, each one of 250 mL, from 70 mothers clubs. To achieve the research objective physical – chemical tests and organoleptic features were performed complying with the provisions of the PTS with respect to density, acidity, protein, fat, dry extract, non-fatty extract, alteration test 97; 96,31; 95,80; 97,62; 91,70; 97,14; 98,20 per cent respectively and adulteration test negative